A peptide tetramer Tk‐tPN induces tolerance of cardiac allografting by conversion of type 1 to type 2 immune responses via the Toll‐like receptor 2 signal‐promoted activation of the MCP1 gene. Issue 3 (16th February 2016) - Li, Zuoqing; Yang, Neng; Zhou, Ling; Gu, Peng; Wang, Hui; Zhou, Yun; Zhou, Peijun; Lu, Liming; Chou, Kuang‐Yen
Summary: The plant protein trichosanthin (Tk) and its derived peptide tetramer Tk‐tPN have been shown to stimulate the type 2 immune responses for treating autoimmune disease. This work explores the possibility of using Tk‐tPN as a non‐toxic immunosuppressant to induce transplantation tolerance using the mechanisms by which T‐cell‐mediated immune responses are transferred from type 1 to type 2 through innate immunity‐related pathways. Immunocytes and cytokine secretions involved in the mouse cardiac allografting model with Tk‐tPN treatment were characterized. Identification of critical genes and analysis of their functions through Toll‐like receptor (TLR) ‐initiated signalling and the possible epigenetic changes were performed. Mean survival times of the cardiac allografts were delayed from 7·7 ± 0·3 days (control) to 22·7 ± 3·9 days ( P < 0·01) or 79·1 ± 19·2 days ( P < 0·0001) when Tk‐tPN was introduced into the recipients alone or together with rapamycin, respectively. The grafting tolerance was donor‐specific. The secretion pattern of the type 1 cytokine/transcription factor (IL‐2 + IFN‐ γ + T‐bet + ), which is responsible for the acute graft rejection, was shifted to the type 2 factor (IL‐4 + IL‐10 + Gata3 + ), together with a selective expansion of the IL‐4/IL‐10‐producing CD8 + CD28 − regulatory T‐cell subset. A TLR2‐initiated high expression of chemokine gene MCP1 was detectable simultaneously. Epigenetically Tk/Tk‐tPN could also acetylate the histone H3K9 of MCP1 promoter to skew the immunity towards T helper type 2 responses. Tk/Tk‐tPN is therefore capable of down‐regulating the type 1 response‐dominant rejection of cardiac allografts by evoking type 2 immunity through the activation of a TLR2‐initiated signalling pathway and MCP1 gene to expand the IL‐4/IL‐10‐secreting CD8 + CD28 − regulatory T cells. Tk‐tPN could be a promising novel immunosuppressant to induce tolerance in allotransplantation.